Characteristics and Application of a Novel Loop Antenna to UHF RFID Receivers - Zijian Xing; Ling Wang; Changying Wu; Jianying Li; Meng Zhang (International Journal of Antennas and Propagation)
A broadband two-layer and two quasihalf loops antenna (TTLA) at UHF is characterized and analyzed for ultrahigh frequency (UHF) near-field radiofrequency identification (RFID) applications. The antenna is investigated in terms of impedance matching and distribution of magnetic field as well as applied in two scenarios which are the experiments of interrogation range and receiver circuit of RFID systems.